Circularly polarized stacked patch antenna array with enhanced bandwidth for S‐band applications. Issue 9 (16th May 2019) - Khan, Muhammad S.; Iftikhar, Adnan; Fayyaz, Ahmad; Asif, Sajid M.; Ijaz, Bilal; Shubair, Raed M.; Khan, Shahid A.
Abstract: In this article, a circularly polarized coupled slot 1 × 4 stacked patch antenna array with enhanced bandwidth is proposed for S‐band applications. Initially, a patch antenna radiating at 2.79 GHz is designed and maximum energy from feedline to patch element is coupled using two rectangular slots. Whereas, a parallel feedline structure is designed to provide polarization flexibility by creating 0, 90, and 180 o phase differences. Then, a truncated patch element is vertically stacked in the design to achieve broader bandwidth of 600 MHz over frequency range from 2.4 to 3.0 GHz. Finally, a coupled slot 1 × 4 array stacked antenna array having feedline line structure to provide 90 o phase difference for circular polarization is designed and fabricated for measurements. It is observed that the final design achieved target specification having impedance matching (| S 11 | (dB) < −10 dB over 2.4 to 3.0 GHz, broad band circular polarization, and 11.5 dBic total gain. Overall, a good agreement between simulated and measurement results is observed.